Wastes to Reduce Emissions from Automotive Diesel Engines. (10th February 2014) - Jiménez Aguilar, Manuel
Abstract : The objective of the study was actually the investigation of the effect of various treatments on the ability of urine in absorbing greenhouse gases. Urine alone or mixed with olive-oil-mill waste waters (O), poultry litter (P), or sewage sludge (S) was used on the absorption of CO2 and NO x from diesel exhaust. The absorption coefficient (0.98–0.29 g CO2 /grNH4 ) was similar to other solvents such as ammonia and amines. The ranges of CO2 absorption(1.7–5.6) g/l and NO reduction (0.9–3.7) g/l in six hours indicate that on average 20 litres of urine could be needed to capture CO2 andNO x vehicle emissions from each covered kilometre. The best results of CO2 absorption andNO x reduction were for urine mixed with O, P and urine alone. These wastes could be used to capture CO2 andNO x from automotive diesel engines to reduce gas emissions. The proposed strategy requires further research to increase CO2 absorption and reduce the risks associated with waste-water reuse.